Defining Action Plans to Reduce Defects in a Paper Production Line Using Statistical Process Control and Fuzzy Analytical Hierarchy Procedure - Susilawati, Anita; Mustafa, Rolandi; Adek Tasri (International Journal of Integrated Engineering, 2025)
Defect prevention in products is essential to improve production efficiency and improve product quality in accordance with consumer expectations. Action plants to prevent defects in a paper factory were tried to be found in this research. The action plan was obtained using Statistical Process Control to control production to comply with specific limits, and Fuzzy Analytical Hierarchy Procedure used to find the priority of the problem. The data collected showed that the primary defects were in the form of wrapping alignment and folding sheets. Analysis showed that wrapper properties and the length of time the wrapper roll on the floor caused the problems. To overcome the causes of the problems, three action plans need to be taken: training, creating SOPs, and creating maintenance checklists.